The relationship between corporate social responsibility disclosure and financial performance in the Iraqi companies: literature review - Azam Abdelhakeem Khalid Ahmed (Tanjong Malim, 2019)
The relationship between corporate social responsibility disclosure and financial performance in the Iraqi companies: literature review by Azam Abdelhakeem Khalid Ahmed